The COVID-19 Pandemic and Sustainability of Development and Peace in Africa - Agunyai, Samuel Chukwudi (Journal of Sustainable Development Law and Policy, 2025)
Contrary to the general opinion that the COVID-19 pandemic is destructive, it presented a mutual agreement situation between conflicting parties in some African states. Although the sustainability of this mutual agreement is difficult to establish, evidence shows that conflicting parties jointly agreed to combat the common enemy called COVID-19 purposefully because the pandemic affects all, including warriors in battle fields. While several studies on this subject are quick to criticize the pandemic as highly destructive, there is very little research on the positive attributes of the pandemic. Drawing on secondary data and state fragility theory, this article examines how the pandemic somehow stimulated development and peace in some conflict-ridden African states. It specifically interrogates how sustainable development and peace were during the pandemic era. The findings reveal the extent to which development and peace have fared amid COVID19 in Africa.